Status and Correlated Factors with Suicidal Ideation Among Patients with Lung Cancer: Evidence from Vietnam - Nguyen Van Tuan; Le Thi Thu Ha; Pham Quang Hung; Le Cong Thien; Doan Thi Hue; Nguyen Hoang Yen; Nguyen Thi Hoa; Le Phu Tai; Nguyen Thanh Long; Pham Xuan Thang; Nguyen Hoang Thanh (Journal of Affective Disorders Reports, 2024)
ABSTRACT: Objective: This study described the rate of suicidal ideation in lung cancer patients and identify associated factors. Method: A cross-sectional study was conducted from August 2021 to October 2022 at the Nuclear Medicine and Oncology Center – Bach Mai Hospital, Hanoi, Vietnam. A total of 256 patients completed the survey. The Columbia Suicide Severity Rating Scale (C-SSRS) was used to measure suicidal ideation. The Hospital Anxiety and Depression Scale (HADS) was utilized to evaluate depression and anxiety. Socio-demographic characteristics, clinical features and pain severity were also measured. Multivariate logistic regression was used to identify factors associated with suicidal ideation. Results: There was 8.2% having suicidal ideation. Among patients with suicidal ideation, the mean score of intensity subscale was 13.33 ± 4.98, and mean scores on intensity scale items were as follows: frequency (mean=2.86 ± 1.32). duration (mean=2.29 ± 1.15), controllability (mean=2.67 ± 1.28), deterrents (mean=2.48 ± 1.21), and reason for ideation (mean=3,05 ± 1,63). Being female (OR=3.36, 95%CI=1.35-8.37), having severxe pain (OR=5.91, 95%CI=1.65-21.18), having depression (OR=10.36, 95%CI=3.93-27.39) and having anxiety (OR=7.81, 95%CI=3.05-20.01) were positively associated with the likelihood of having suicidal ideation among lung cancer patients. Conclusion: Findings revealed the high prevalence of suicidal ideation among individuals diagnosed with lung cancer in Vietnam. Notably, this trend was more pronounced among female patients, those with severe pain, and individuals experiencing mental disorders such as depression and anxiety. Practitioners ought to prioritize the screening and intervention processes for lung cancer patients with a high risk of suicidal tendencies.